The role of drug regulatory authorities and health technology assessment agencies in shaping incentives for antibiotic R&D: a qualitative study - Cecilia Kållberg; Liv Mathiesen; Unni Gopinathan; Hege Salvesen Blix (Journal of Pharmaceutical Policy and Practice, 2023)
Abstract Background Few antibiotics have entered the market in recent years despite the need for new treatment options. Some of the challenges of bringing new antibiotics to market are linked to the marketing authorization and health technology assessment (HTA) processes. Research shows great variation in geographic availability of new antibiotics, suggesting that market introduction of new antibiotics is unpredictable. We aimed to investigate regulatory authorities’ and HTA agencies’ role in developing non-financial incentives to stimulate antibiotic research and development (R&D). Methods We conducted individual, semi-structured, stakeholder interviews. Participants were recruited from regulatory authorities (EMA and FDA) and HTA agencies in Europe. Participants had to be experienced with assessment of antibiotics. The data were analyzed using a deductive and inductive approach to develop codes and identify key themes. Data were analyzed using thematic analysis including the constant comparison method to define concepts, and rival thinking to identify alternative explanations. Results We found that (1) interpretation of key concepts guiding the understanding of what type of antibiotics are needed vary (2) lack of a shared approach on how to deal with limited clinical data in the marketing authorization and HTA processes is causing barriers to getting new antibiotics to market (3) necessary adaptations to the marketing authorization process causes uncertainties that transmit to other key stakeholders involved in delivering antibiotics to patients. Conclusions A shared understanding of limited clinical data and how to deal with this issue is needed amongst stakeholders involved in antibiotic R&D, marketing authorization, and market introduction to ensure antibiotics reach the market before resistance levels are out of control. Regulatory authorities and HTA agencies could play an active role in aligning the view of what constitutes an unmet medical need, and direct new economic models towards stimulating greater diversity in the antibiotic armamentarium.